2021
DOI: 10.3390/app112411937
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of Chitosan for Antibacterial Applications—Current Trends

Abstract: Chitosan is a natural biopolymer that can be suitable for a wide range of applications due to its biocompatibility, rigid structure, and biodegradability. Moreover, it has been proven to have an antibacterial effect against several bacteria strains by incorporating the advantages of the electrospinning technique, with which tailored nanofibrous scaffolds can be produced. A literature search is conducted in this review regarding the antibacterial effectiveness of chitosan-based nanofibers in the filtration, bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 206 publications
(260 reference statements)
1
21
0
Order By: Relevance
“…64 Therefore, high acid concentrations are needed (70–90%) with low to medium molecular weights to generate pure chitosan fibers or, more commonly, polymeric blends with either hydrophilic polymers (polyethylene oxide (PEO), PVA) or hydrophobic polymers (PCL, Nylon) are used to decrease repulsion by hydrogen bonding. 65,66…”
Section: Electrospinning With Green Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…64 Therefore, high acid concentrations are needed (70–90%) with low to medium molecular weights to generate pure chitosan fibers or, more commonly, polymeric blends with either hydrophilic polymers (polyethylene oxide (PEO), PVA) or hydrophobic polymers (PCL, Nylon) are used to decrease repulsion by hydrogen bonding. 65,66…”
Section: Electrospinning With Green Solventsmentioning
confidence: 99%
“…64 Therefore, high acid concentrations are needed (70-90%) with low to medium molecular weights to generate pure chitosan fibers or, more commonly, polymeric blends with either hydrophilic polymers (polyethylene oxide (PEO), PVA) or hydrophobic polymers (PCL, Nylon) are used to decrease repulsion by hydrogen bonding. 65,66 Geng et al electrospun CS fibers with an average diameter of 130 nm from aqueous 90% AcOH solution containing 7 wt% of polymer. The authors reported that the acid content should be higher than 30%, a requirement for CS fiber formation, because more concentrated acetic acid decreased surface tension of the CS solution and increased charge density.…”
Section: Polymers Electrospun With Green Solventsmentioning
confidence: 99%
“…Chitosan has been vastly exploited for the treatment of acute and chronic wounds, because it can stimulate hemostasis and induce tissue regeneration [ 163 , 164 ]. Furthermore, it exhibits antimicrobial activity against a wide variety of bacteria and fungi due to its cationic nature, which is influenced by the degree of deacetylation and molecular weight [ 165 , 166 ]. Already, chitosan-based wound dressings exist commercially in the form of hydrogels, sponges, films, and nonwovens [ 164 ].…”
Section: Marine Animal-derived Biopolymersmentioning
confidence: 99%
“…Despite the high potential of CS and HA for regenerative medicine applications, electrospinning pure polymeric solutions is difficult because of their insufficient rheological properties, high surface tension, limited solubility, and poor mechanical characteristics . To overcome the electrospinning limitations of natural polymers and the repulsion forces between the charged groups, electrospinning was performed using composite nanofibers from natural and synthetic polymers .…”
Section: Introductionmentioning
confidence: 99%